2006
DOI: 10.1016/j.nut.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Food items consumed by students attending schools in different socioeconomic areas in Cape Town, South Africa

Abstract: The large majority of food eaten by adolescent students in Cape Town is classified as being unhealthy choices. This applies to foods brought to school and food purchases. Consideration needs to be given to policy measures to improve this situation and to improve education of students and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 20 publications
(20 reference statements)
9
82
2
1
Order By: Relevance
“…Previous studies have shown that learners who attended schools of high socio-economic status were twice as likely to bring food to school (13) and that learners from rural and disadvantaged settings were less likely to bring a lunch box to school because of a lack of food available at home (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that learners who attended schools of high socio-economic status were twice as likely to bring food to school (13) and that learners from rural and disadvantaged settings were less likely to bring a lunch box to school because of a lack of food available at home (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Various local studies show that most foods purchased at schools came from the tuck shop and were classified as unhealthy items (32)(33)(34) . Changing school tuck shops to healthier ones would provide learners with the opportunity to make healthier food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in peri-urban settlements in South Africa follow problematic diet regimes that consist of an excessive intake of saturated fats, calories, salt, sugar, and animal proteins, and the insufficient intake of fibre and essential vitamins and minerals − caused by minimal fruit, vegetable, and dairy consumption (MacIntyre, Kruger, Venter, & Vorster, 2002;Mungai-Singh, 2012;Sacks et al, 2001;Steyn, Katzenellenbogen, Lombard, & Bourne, 1997;Temple, Steyn, Myburgh, & Nel, 2006). This diet directly opposes the nutrition guidelines provided by The South African Hypertension Guideline (2011), which 1 immediately adjoining an urban area usually comprising of low income housing and mixed formal and informal settlements emphasises the adoption of a diet that is low in total and saturated fat, caffeine, salt, and sugar, and high in fibre, low-fat dairy products, vitamins, and minerals (Appel et al, 1997;Seedat & Rayner, 2011).…”
Section: Dietary Patterns In Peri-urban South African Settlementsmentioning
confidence: 99%